A troponin study on patients with ischemic stroke, intracerebral hemorrhage and subarachnoid hemorrhage: Type II myocardial infarction is significantly associated with stroke severity, discharge disposition and mortality. (June 2019) - Alkhachroum, Ayham M.; Miller, Benjamin; Chami, Tarek; Tatsuoka, Curtis; Sila, Cathy
Highlights: High troponin levels were associated with higher NIHSS in ischemic stroke patients. High troponin in ischemic stroke patients were associated with higher mortality. High troponin levels were associated with worse discharge disposition. Abstract: Troponin elevations due to Type II myocardial infarction (T2MI) are associated with hemorrhagic and ischemic strokes but there is little data on stroke severity, troponin elevation and outcome. We studied 1655 patients from a tertiary medical center between 1/2013-4/2015 using multivariate regression analysis for demographics, vascular risk factors, admission stroke severity, laboratory tests, echocardiogram results and discharge disposition. Troponin levels were classified as normal <0.04 ng/ml and high >0.04 ng/ml (critical if >0.5 ng/ml). A T2MI was diagnosed by a trending troponin elevation; patients with type I MI, patients with subdural and epidural hematoma, or hemorrhagic metastatic disease and patients younger than 18 years old were excluded. We had 818 patients with ischemic stroke, 306 with intracerebral hemorrhage (ICH) and 169 with subarachnoid hemorrhage (SAH). Troponin was elevated (>0.04 ng/ml) in 24.1% of ischemic stroke patients, 27.1% in the ICH group, and in 39% of SAH patients. High initial and peak troponin levels were associated with higher National Institutes of Health Stroke Scale (NIHSS) in patients with ischemic stroke (OR 1.04; CI 95%, 1.02–1.07, p = .001) and (OR 1.05; CI 95%, 1.03–1.07, p < .001). In ICH patients, higher initial and peak troponin levels were not associated with worse ICH scores (OR 1.21; CI 95%, 0.66–2.22, p = .53) and (OR 1.36; CI 95%, 0.77–2.41, p = .29). In SAH patients, higher initial and peak troponin levels was associated with higher Hunt and Hess scores (OR 4.2; CI 95%, 1.6–11.4, p = .005) and (OR 3.14; CI 95%, 1.5–6.5, p = .002). In patients with high troponin levels mortality was 14.7% in ischemic stroke patients, 31.3% in our ICH patients, and 43.8% in our SAH. After adjusting for demographics and clinical risk factors, only high troponin ischemic stroke patients were associated with higher mortality (OR 6.16; CI95%, 2.46–15.4, p < .001), and worse discharge disposition (OR 2.3; CI 95%, 1.19–4.45, p = .01). High troponin levels were not associated with change of outcomes in patients with SAH and ICH after adjusting for demographics and clinical risk factors. Elevated troponin due to T2MI is common in patients with ischemic strokes, ICH, and SAH. It is significantly associated with stroke severity, poor discharge disposition, and high mortality. Troponin levels should be considered on admission for acute strokes.